A colorimetric sensor array for the discrimination of Chinese liquors. Issue 21 (28th August 2020) - Sun, Shan; Qian, Sihua; Zheng, Jianping; Li, Zhongjun; Lin, Hengwei
Abstract : A simple colorimetric sensor array method is developed to identify various Chinese liquors in the liquid phase without the aid of other analytical techniques. Abstract : Although some colorimetric sensor arrays have been developed for the identification of Chinese liquors, they usually require the confirmation of volatile markers in the liquors by chromatography and mass spectrometry firstly. Herein, we present a simple colorimetric sensor array to identify various Chinese liquors in the liquid phase without the aid of other analytical techniques. The colorimetric sensor array consists of six commercially available and inexpensive solvatochromic dyes, and the sensing mechanism of this array is based on the response of solvatochromic dyes to their local polarity. On the basis of the colour changes of the sensor array, different Chinese liquors are discerned readily using pattern recognition methods, and the statistical analysis results ( i.e., hierarchical clustering analysis and principal component analysis) reveal that the as-fabricated sensor array can distinguish the subtle differences between different liquors from the same winery and the same flavor type. Moreover, the developed sensor array can even distinguish diverse diluted liquors from the pristine ones.